Do stone size and impaction influence therapeutic approach to proximal ureteral stones? - Radulović Slobodan; Vuksanović Aleksandra; Milenković-Petronić Dragica; Vavić Božo (Vojnosanitetski Pregled)
Background/Aim. Primary therapeutic approach to lumbar ureteral stones is still contraversial. The aim of the study was to investigate the influence of stone impaction and size on the effectiveness of proximal ureteral stone lithotripsy. Methods. A total of 123 patients with proximal ureteral stones were investigated in this prospective study performed in a 10- month period. The patients were divided into the group I - 86 patients treated with extracorporeal shock wave lithotripsy (ESWL) and the group II - 37 patients treated with 'Swiss' Lithoclast. In the group I, 49 stones (57%) were classified as impacted, while 20 stones (23.3%) were larger than 100 mm2. In the group II, 26 stones (70.3%) were impacted, and 11 stones (29.7%) were larger than 100 mm2. Stones were defined as impacted by the radiographic, echosonographic as well as endoscopic findings in the group II of patients. Stone size was presented in mm2. Chemical composition of stones were almost the same in both groups of the patients. Results. Generally, there was no statistically significant difference in the treatment success between the groups. However, stones larger than 100 mm2 were statistically more successfully treated endoscopically, while there was no statistical difference in the treatment success of impacted stones between these two groups. Conclusion. ESWL can by considered as primary first therapeutic approach in treatment of all proximal ureteral stones except for stones larger than 100 mm2 that should primarily be treated endoscopically.